Work-Life Balance, Learning Agility and Their Impact on Work Stress of Employees who Work From Home - Indah Rizki Maulia; Windy Widiyawati; Fitri Diana (Universitas Pamulang, 2023)
Work stress is one of the factors that can lower immunity. The WFH (work from home) policy is made so that the working community can avoid Covid-19, but it becomes counter-productive if employees who undergo WFH experience stress and their immunity decreases. This research was conducted using correlational quantitative methods to examine the impact of work-life balance and learning agility on the work stress of employees who have to work from home during the Covid-19 pandemic. The research subjects/respondents were company employees in the Jakarta area who underwent WFH during the Covid-19 pandemic as many as 57 respondents using incidental sampling. Data analysis using SEM-PLS and obtained the results: (1) There is a significant direct impact of work-life balance on the work stress of employees who undergo WFH; (2) There is a significant direct impact of learning agility on the work stress of employees undergoing WFH